2012
DOI: 10.1007/bf03396953
|View full text |Cite
|
Sign up to set email alerts
|

The Pedagogical, Linguistic, and Content Features of Popular English Language Learning Websites in China: A Framework for Analysis and Design

Abstract: As increasing numbers of Chinese language learners choose to learn English online, there is a need to investigate popular websites and their language learning designs. This paper reports on the first stage of a study that analyzed the pedagogical, linguistic, and content features of 25 Chinese English Language Learning (ELL) websites ranked according to their value and importance to users. The website ranking was undertaken using a system known as PageRank. The aim of the study was to identify the features cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Nelson, one interviewee, added that using the Chinese language with the English translation or vice versa was also acceptable. This finding resonates with what was reported in a recent study (Kettle, et al, 2012), that the informative and directive language used by ELL websites, affects learners' choice of websites to some degree. This is contrary to a common perception that EFL learners prefer the use of the target language as the language of instruction or navigation (Liu et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Nelson, one interviewee, added that using the Chinese language with the English translation or vice versa was also acceptable. This finding resonates with what was reported in a recent study (Kettle, et al, 2012), that the informative and directive language used by ELL websites, affects learners' choice of websites to some degree. This is contrary to a common perception that EFL learners prefer the use of the target language as the language of instruction or navigation (Liu et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, it was found that the high ranking websites, such as Hu Jiang English (Level 7), New Oriental Online (Level 7), 51 IETLS (Level 6), and Big Ear English (Level 6), were among the common websites that the interviewees had utilized to access various teaching materials (see Table 3). Kettle, et al (2012) believed that these websites suited Chinese pedagogical needs as they were highly examination-oriented, with ample materials and tasks for users to practise both discrete language items and related examination skills. Learners of different levels can find a variety of learning materials to satisfy their individual learning needs and examination preparation (see Section 4.2).…”
Section: Discussionmentioning
confidence: 99%
“…In China, American English has gained huge popularity that has led to a growing number of language schools in China and a large number of Internet sites for learning English (Kettle et al 2012). English language education has become one of the elements that schools in China are evaluated on (Jie and Xiaoqing 2006).…”
Section: Chinese International Student Challengesmentioning
confidence: 99%
“…English has gained huge popularity in China, and has become a key indicator for school performance (Jie & Xiaoqing, 2006). This trend has increased the popularity of English language schools in China and the development of countless internet resources (Kettle, Yuan, Luke, Ewing, & Shen, 2012). Additionally, it is very common to see high school student organizations hosting English corners to help practice English language skills (Gao, 2012).…”
Section: Current Preparation For Chinese International Studentsmentioning
confidence: 99%